Ethnic Differences in Abstinence Self-Efficacy among Recovering Individuals - Elbia Navarro; Josefina Alvarez; Richard Contreras; Leonard A Jason (Journal of Addiction Medicine and Therapeutic Science - Peertechz Publications, 2016)
According to the 2010 Census, Latinos comprise 16.3% of the total U.S. population. This group continues to grow and by the year 2050, Latinos are expected make up 25% of the total U.S. population [1]. National surveys indicate that this group engages in substance use behavior at similar rates to the national  average [2], but have higher rates of substance related problems compared to other groups [3]. Current research indicates that Latinos underutilize substance abuse treatment [4-6], but the reasons for this groups' treatment underutilization are not well-understood. Socio-demographic characteristics are associated with substance abuse treatment utilization among Latinos. In particular, individuals who are younger, have lower incomes and who have no health insurance are least likely to use mental health and substance use services [7]. English speaking and U.S. born Latinos are more likely to utilize substance abuse treatment compared to their immigrant and Spanish-speaking counterparts [8,9]. Pubmed link: https://www.ncbi.nlm.nih.gov/pubmed/28840200